Technology and professionalism are tools that help us improve results in assisted reproductive technology - Gazzo Benavides, Eduardo (2019)
In recent years, the demand for assisted reproduction procedures has increased considerably. Everything seems to indicate that this trend will continue along this same path, which forces professionals in the reproductive area to be up to date with the latest advances in technology and personnel preparation, with the sole purpose of offering patients better pregnancy rates. The current goal of assisted reproduction is to achieve pregnancy and that it comes to an end after the first transfer of a single embryo. This is a great challenge, since it implies the joint effort to ensure that the majority of our patients achieve the desired healthy baby at home. Therefore, for a few years we assumed this commitment and understood that the only way to achieve this goal was to use all the available tools that technology can offer us in the reproductive field.